Socioeconomic status and incidence of type –II diabetes - A. NIRMALA; MAZHER SULTANA; N.S. JAGADEESWARI (International Journal of Pharma and Bio Sciences, 2018)
Diabetes is often referred to Diabetes Mellitus, a group of metabolic disease characterized by hyperglycemia resulting from defects in insulin secretion, insulin action or both. The risk of type 2 diabetes (T2DM) increases with lower socioeconomic position. Hence, people with low educational level, low income level, low occupational status or people with adverse socioeconomic conditions have higher risk of developing T2DM than people with higher socioeconomic position. Diabetic individuals spending more money towards high quality health care treatment or reducing the progression of diabetic related complications. Prevention seems to be the need of the hour to tackle this epidemic issue. This article highlights the social and economic implications of diabetes in India and emphasizes the measures required to prevent diabetes.